Marketing Communication Program Design of Online Travel Agent Kliktrip Using Benchmarking and Analytical Hierarchy Process Methods - Alviera Suci Damayanti; Sari Wulandari; Meldi Rendra (School of Industrial and System Engineering, Telkom University, 2021)
Kliktrip is an Online Travel Agent (OTA) that has trip & activities facilities and was established in 2018 in Bandung. Kliktrip sales are still experiencing a decline due to low public awareness of Kliktrip which is seen through the number of downloads on mobile apps and Instagram followers. Kliktrip sales are still experiencing a decline and public awareness of Kliktrip is still low because Kliktrip has not implemented 7 out of 8 marketing communication mix optimally. Therefore, research was conducted to design an effective marketing communication program for Kliktrip by using benchmarking and Analytical Hierarchy Process (AHP) methods. Based on the results of AHP data processing, it can be seen that the selected benchmark partner is Explorer.id with a total priority vector value of 0.44 and benchmark results with Explorer.id concluded that Kliktrip needs to increases the value of SEO, page views, and unique visitors on the website, creates a Tiktok’s account, webisode, and video podcasting, collaborates with cross-promotion, makes contests (giveaways), increase the number of downloads and reviewers on mobile apps, implementing mobile billboards and cause-related marketing, increasing customer service operational time, participating in exhibitions, and collaborating with influencers.